Molecular and Genetic Bases of Mammalian Maternal Behavior. (5th February 2019) - Fleming, Alison S.; Kraemer, Gary W.
New mammalian mothers undergo an increase in their maternal responsiveness with the birth of their infants. Associated with changes in responsiveness are how attracted mothers are to infant cues, mothers' affective state, and their cognitive and executive function. In comparison to nonmothers, new mothers are more attracted to infant odors and are more easily alerted to their vocalizations; they undergo a reduction in withdrawal behaviors and anxiety, but increased lability. Their maternal sensitivity (human or licking intensity, rat) is associated with higher levels of attention and working memory. Maternal responsiveness and these associated behaviors are associated with large shifts in maternal hormones across parturition. Changes in expression of neuropeptides and neurotransmitters are affected by mothers' prior experiences, including their very early experiences in their families of origin. The present review describes the regulation of mothering and associated behaviors by the neurotransmitters, oxytocin, dopamine, and serotonin, in a rat model and in humans. Emphasis is then given to studies that focus on the role of genes and what we know about their expression in the functioning of these 3 neurochemical systems in new mothers. Studies of early experience, genetics, and human mothering show gene-by-environment interplays (interactions) for a number of DNA single-nucleotide polymorphism within both the oxytocin and serotonin systems, where associations between mothers' early experiences and mothering/affect depend on mothers' genotype. Studies also show associations between different dopamine genes and many aspects of both mothering and maternal affect. Where known, we also discuss evidence that the relation between early experience and mothering is often an indirect one, mediated through an effect of experience on mothers' affect or executive function. In many cases, mothers' genetic profile moderates these relations. Finally, preliminary evidence suggests a role of epigenetic mechanisms in these processes.